CAK KISAH SENI MAGIS PERINTIS PERTUNJUKAN TURISTIK - Kadek Suartaya (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2004)
As a performing art form, Cak was designed as an aesthetical presentation to be performed before an audience. It originated in the village of Bedulu, a place also known for its traditional ritual dances, Sanghyang Dedari and Sanghyang Jaran, for keeping away evil spirits.Artist (painter) WaIter Spies, who had the idea for this dance and the dancer Baris I Wayang Limbak, who was the main creator and performer. are the two people responsible for creating a performing art work adopted from the sacred religious rituals mentioned above. The excess of tourists which followed the journey of Cak in Bedulu led to its development in the neighboring village of Bona, Gianyar.Although it has been adopted as a tourist perfo'rmance, the tradition of performing Sanghyang in a religious context still continues in the village of Bona. Therefore, Cak still exists as an accompaniment to Sanghyang for various religious rituals, in particular the dewa yadnya ceremony (offering a holy sacrifice to the gods) and the buta yadnya ceremony (offering a holy sacrifice to the evil spirits)Key words: Cek, tourist performance, magic.